2021
DOI: 10.3390/jcm10194562
|View full text |Cite
|
Sign up to set email alerts
|

The Netherlands Is on Track to Meet the World Health Organization Hepatitis C Elimination Targets by 2030

Abstract: Background: The Netherlands strives for hepatitis C virus (HCV) elimination, in accordance with the World Health Organization targets. An accurate estimate when HCV elimination will be reached is elusive. We have embarked on a nationwide HCV elimination project (CELINE) that allowed us to harvest detailed data on the Dutch HCV epidemic. This study aims to provide a well-supported timeline towards HCV elimination in The Netherlands. Methods: A previously published Markov model was used, adopting published data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…CELINE results must be placed in the greater context of HCV elimination. A recent modelling study predicting the Netherlands' progress towards the WHO HCV elimination targets concluded that the Netherlands is currently on track to meet these targets by 2030 [11]. However, this was only met under the assumption that annual HCV diagnosis and treatment rates were maintained at the 2019 levels.…”
Section: Discussionmentioning
confidence: 99%
“…CELINE results must be placed in the greater context of HCV elimination. A recent modelling study predicting the Netherlands' progress towards the WHO HCV elimination targets concluded that the Netherlands is currently on track to meet these targets by 2030 [11]. However, this was only met under the assumption that annual HCV diagnosis and treatment rates were maintained at the 2019 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, the introduction of direct-acting antiviral (DAA) drugs in clinical practice has significantly increased the rate of people who have eradicated the virus, although a small percentage of positive patients are still difficult to treat [ 2 ]. The HCV eradication program is ongoing, even if the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has created a delay in the diagnosis and cure of patients with HCV infection due to a reallocation of public health measures and resources [ 3 , 4 ]. Van Dijk and co-authors, by applying a mathematical model, have shown an increased number of hepatic diseases during the COVID-19 pandemic scenario [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HCV eradication program is ongoing, even if the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has created a delay in the diagnosis and cure of patients with HCV infection due to a reallocation of public health measures and resources [ 3 , 4 ]. Van Dijk and co-authors, by applying a mathematical model, have shown an increased number of hepatic diseases during the COVID-19 pandemic scenario [ 4 ]. However, timely diagnosis and DAA treatment has reduced the pathogenic effects of a persistent HCV infection, in both hepatic and extra-hepatic diseases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the World Health Organization (WHO) set ambitious goals for the elimination of HBV and HCV by 2030 [5]. Key to the target in this elimination strategy are specific populations, where the prevalence rates are higher, in particular migrants from endemic countries and people who inject(ed) drugs (PWID) [4,6]. For instance, in the Netherlands prevalence rates for HBV and HCV among PWID are up to 4% and 59%, respectively [4].…”
Section: Introductionmentioning
confidence: 99%